Racial Disparities in Stillbirth Risk Factors among non-Hispanic Black Women and non-Hispanic White Women in the United States. Issue 6 (November 2021) - Henry, Carrie J.; Higgins, Melinda; Carlson, Nicole; Song, Mi-Kyung
Abstract: Introduction: Historically, stillbirth risk factors are more prevalent among non-Hispanic Black women than non-Hispanic White women, including age < 20, lower formal educational attainment, prepregnancy obesity, smoking, hypertension, diabetes, short interpregnancy interval, small for gestational age newborn, late prenatal care, and previous cesarean birth. We examined whether these disparities have changed since 2011 and identified a group of risk factors that differed between Black women and White women when accounting for correlations among variables. Methods: In a random sample of 315 stillbirths from the National Center for Health Statistics' 2016 fetal death data, Black women and White women were compared for each risk factor using t -tests or chi-square tests. Variables with p ⩽ .20 were analyzed using multivariate analysis of variance. Results: In this sample, Black women experiencing stillbirth were less likely to have a Bachelor's degree (12.94% vs. 28.49%, p = .04), and more likely to be obese (44.5% vs. 29.1%, p = .01) than White women. Multivariate analysis accounting for correlations among variables showed a group of risk factors that differed between Black women and White women: age < 20, lower education, prepregnancy obesity, hypertension (chronic and pregnancy-associated), nulliparity before stillbirth, and earlier gestation. Clinical Implications: Less formal education, obesity, age <20, hypertension, chronic and pregnancy-associated, nulliparity, and earlier gestation are important to consider in multilevel stillbirth prevention interventions to decrease racial disparity in stillbirth. Respectfully listening to women and taking their concerns seriously is one way nurses and other health care providers can promote equity in health outcomes for childbearing women. Abstract : Non-Hispanic Black women in the United States are at increased risk for stillbirth when compared to non-Hispanic White women. This study used vital statistics data to highlight health disparities in maternity outcomes. Recommendations for improvement in maternity care are included.